2016
DOI: 10.1080/19325037.2016.1178610
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three Osteoporosis Prevention Programs for Young Women: Application of the Health Belief Model

Abstract: Purpose: The purpose of this study was to evaluate the effectiveness of theory-based osteoporosis prevention programs on calcium and vitamin D intakes and osteoporosis health beliefs in young women. Methods: Women (N ¼ 152) aged 19 to 25 years were randomly assigned to one of 3 groups: a brochure group (n ¼ 51), a computer-tailored program group (n ¼ 51, and the same computer-tailored program (n ¼ 50) with brief verbal feedback. Participants completed surveys regarding osteoporosis beliefs prior to and immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Even though the mean score of the barriers' was increased somewhat during the follow-up stage of the program,the result still significant; these could be attributed to the cost of calcium diet as mentioned by the participants. This is consistent with studies of Lein et al, (27) and Khorsandi et al, (28) who found that perceived barriers regarding calcium intake and exercise decreased after the intervention.…”
Section: Discussionsupporting
confidence: 93%
“…Even though the mean score of the barriers' was increased somewhat during the follow-up stage of the program,the result still significant; these could be attributed to the cost of calcium diet as mentioned by the participants. This is consistent with studies of Lein et al, (27) and Khorsandi et al, (28) who found that perceived barriers regarding calcium intake and exercise decreased after the intervention.…”
Section: Discussionsupporting
confidence: 93%
“…However, in the third stage of the study (3 months after intervention), the value of received calcium reduced. In a study by Lein, Turner, and Wilroy (2016), after educational intervention, the average score of received calcium improved and the average score of perceived barriers reduced. Shobeiri, Hesami, Khodakarami, and Soltanian (2015) investigated the effect of consultation on prevention behaviors from osteoporosis in women who were referred to health centers in Hamedan, Iran.…”
Section: Discussionmentioning
confidence: 98%
“…Multiple studies have shown that it is urgent for providers to educate patients on preventative behaviors such as eating a healthy diet and regular exercise. 2,4,[13][14][15] Several studies demonstrated that osteoporosis may be preventable if prevention begins in early adulthood. 4,13,14 All studies concluded that women have better outcomes if they are knowledgeable about osteoporosis and its risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,[13][14][15] Several studies demonstrated that osteoporosis may be preventable if prevention begins in early adulthood. 4,13,14 All studies concluded that women have better outcomes if they are knowledgeable about osteoporosis and its risk factors. 2,4,[13][14][15][16] In at least 1 study, the perceptions and efforts placed on modifying risk factors, such as nutrition along with calcium and vitamin D intake, were dependent on the younger adult's beliefs on osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation